ONE STEP PURIFICATION OF GLUTAMINASE FREE LASPARAGINASE FROM ERWINIA CAROTOVORA WITH ANTICANCEROUS ACTIVTY: Pharmaceutical Science-Biotechnology - DEVI, SARITA; AZMI, WAMIK (International Journal of Life Science and Pharma Research, 2012)
L-asparaginase is an enzyme that catalyzes the conversion of L-asparagine to L-aspartate and ammonia. The important application of the L-asparaginase enzyme is in the treatment of acute lymphoblastic leukemia, Hodgkin disease, acute myelocytic leukemia, chronic lymphocytic leukemia, lymphosarcoma treatment, reticulosarcoma and melanosarcoma. In the present study, the L-asparaginase from Erwinia carotovora MTCC 1428 was purified and used for the killing of Hep-2C cell line. Sonication of the resting cells was carried out to release the intracellular L-asparaginase and cell free extract was subjected to acid precipitation. Sulphopropyl Sephadex was used for further purification of enzyme. The 24% yield of the Lasparaginase was obtained after single step purification. The specific activity of the purified enzyme was found to be 0.37 IU/mg and the electrophoresis results suggest that the L-asparaginase of E. carotovora MTCC 1428 exists in the form of dimmer of dimmers. Moreover, the purified L-asparaginase from E. carotovora MTCC 1428 do not possess any glutaminase activity. The L-asparaginase purified from E. carotovora MTCC 1428 showed better in vitro toxicity on Hep-2C cell lines (84% survival) in comparison to commercial L-asparaginase preparation (90% survival) obtained from E. coli.